The impact of the electronic medical record on structure, process, and outcomes within primary care: a systematic review of the evidence - Holroyd-Leduc, Jayna M (BMJ Group, 2011)
BACKGROUND: The electronic medical record (EMR)/electronic health record (EHR) is becoming an integral component of many primary-care outpatient practices. Before implementing an EMR/EHR system, primary-care practices should have an understanding of the potential benefits and limitations. OBJECTIVE: The objective of this study was to systematically review the recent literature around the impact of the EMR/EHR within primary-care outpatient practices. MATERIALS AND METHODS: Searches of Medline, EMBASE, CINAHL, ABI Inform, and Cochrane Library were conducted to identify articles published between January 1998 and January 2010. The gray literature and reference lists of included articles were also searched. 30 studies met inclusion criteria. RESULTS AND DISCUSSION: The EMR/EHR appears to have structural and process benefits, but the impact on clinical outcomes is less clear. Using Donabedian's framework, five articles focused on the impact on healthcare structure, 21 explored healthcare process issues, and four focused on health-related outcomes.